Interface design guidelines of nutritional information application for the elderly - Tan, Li Yin; Nazlena Mohamad Ali,; Shahrul Azman Mohd Noah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this study is to evaluate the interface design of nutrition information application for elderly people. Obtaining the proper nutritional information is an important aspect for elderly healthcare. Most information on healthcare can be found from the Internet. However, many elderly people face problems when using the Internet due to their inability to adapt to common platforms of interface design. Due to deterioration in physiological functions, elderly users have different requirements from adult users. A high fidelity prototype on nutrition was developed, taking into consideration the evaluation results from the initial need assessment focus group study. A questionnaire survey was conducted involving 30 respondents aged between 60 and 79 years old. The result reveals that most of the respondents gave a positive feedback to the three main features of interface design, which are simplicity (96%), directness (90%) and consistency (100%). Based on this outcome, it can be concluded that the interface design is well accepted by the elderly respondents.